Servqual dalam Pelayanan Kelas pada Laboratorium Manajemen - Haryadi Sarjono; Natalia Natalia (Binus Business Review, 2014)
This study aims to determine how the quality service class of Laboratory School of Business Management (SoBM), Bina Nusantara University to students majoring in management science to management courses (Quantitative Business Analysis). SoBM has 3 campuses spreading across West Jakarta and Tangerang, which are as much as 2 campuses in West Jakarta and 1 campus in Alam Sutra area (Tangerang). The research was only conducted on campus Alam Sutra (Tangerang) which is relatively new, consisted only 1 class (42 students) that the specialization is entrepreneurship management science courses. This study applied Servqual method which is a measure of customer satisfaction through gap analysis, developed by Parasuraman, Zeithaml, and Berry. Respondents in this study consisted of 42 students who all as population. The results showed that all Servqual dimensions have an unsatisfactory quality. This can be seen from all the negative gaps in dimension tangibles, reliability, responsiveness, assurance and empathy. From all the negative values, reliability dimension(-6.58) has a gap with the highest negative value or the least satisfactory quality.